Diddensiella parasantjacobensis f.a., sp. nov., a yeast species from forest habitats. Issue 3 (29th March 2023) - Dlauchy, Dénes; Lee, Ching-Fu; Yurkov, Andrey M.; Péter, Gábor
Abstract : Six conspecific yeast strains, representing an undescribed species, were isolated from rotten wood collected in different locations in Hungary and Germany and an additional one from fungal fruiting body in Taiwan. The seven strains share identical nucleotide sequences in the D1/D2 domain of the nuclear large subunit (LSU) rRNA gene. The Hungarian and Taiwanese isolates share identical internal transcribed spacer (ITS) sequences as well, while the two German isolates differ from them merely by three substitutions and four indels in this region. The investigated strains are very closely related to Diddensiella santjacobensis . Along their LSU D1/D2 domain they differ only by one substitution from the type strain of D. santjacobensis . However, in the ITS region of Hungarian and Taiwanese strains we detected 3.5 % divergence (nine substitutions and nine indels) between the undescribed species and D. santjacobensis, while the German strains differed by 13 substitutions and nine indels from D. santjacobensis . This ITS sequence divergence has raised the possibility that the strains investigated in this study may represent a different species from D. santjacobensis . This hypothesis was supported by comparisons of partial translation elongation factor 1-α (EF-1α) and cytochrome oxidase II (COX II) gene sequences. While no difference and 1–2 substitutions among the partial EF-1α and COX II gene sequences of the strains of the undescribed species, respectively, were detected; the undescribed species differ by about 4 % (36 substitutions) and 10 % (50–51 substitutions) from D. santjacobensis in these regions. Parsimony network analysis of the partial COX II gene sequences also separated the investigated strains from the type strain of D. santjacobensis . In this paper we propose Diddensiella parasantjacobensis f.a., sp. nov. (holotype: NCAIM Y.02121; isotypes: CBS 17819, DSM 114156) to accommodate the above-noted strains.